Transforming Fiqh Instruction Through the Cyber Scientific Approach: Enhancing Critical Thinking in Islamic Education - Sapiudin Sapiudin; Nur Luthfi Rizqa Herianingtyas; Yanti Herlanti; Syihaabul Hudaa; Muhammad Barid Nizarudin Wajdi; Luo Ying (Jurnal Ilmiah Peuradeun, 2026)
Fiqh learning in Indonesia has traditionally relied on lecture-based instruction rooted in pesantren pedagogy, which often prioritizes knowledge transmission over analytical engagement. This approach, while culturally embedded, poses challenges for cultivating critical thinking skills in 21st-century education. This study introduces the Cyber Scientific Approach (CSA), an instructional model that integrates the scientific method with guided cyber exploration to promote inquiry-based, student-centered learning in Fiqh classrooms. Employing a mixed-methods design, the research involved 60 senior secondary students across three grade levels, combining qualitative data from classroom observations and interviews with quantitative analysis of pre-test and post-test assessments using FRISCO indicators. CSA was implemented through a seven-stage process encompassing Observation, Questioning, Cyber Exploration, Association, Experimentation, Communication, and Conclusion. The findings demonstrate moderate but consistent improvements in students’ critical thinking skills across all grades, evidenced by statistical gains and enhanced classroom engagement. This study offers a structured pedagogical framework that aligns the normative foundations of Islamic jurisprudence with contemporary cognitive and digital competencies. It contributes to advancing Islamic education by providing an empirically grounded model for integrating critical thinking and technology in value-laden curricula.